Prescribing patterns of statins and associated factors among type 2 diabetes mellitus patients attended at Jugol General Hospital in eastern Ethiopia: A cross-sectional study - Nigussie, Shambel; Demeke, Fekade (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background Most clinical practice guidelines support the use of statins in patients with type 2 diabetes mellitus to lower the risk of cardiovascular disease. However, nothing is known about the prescribing patterns of statins at Jugol General Hospital in eastern Ethiopia. Objective This study aimed to assess the prescribing patterns of statins and associated factors among type 2 diabetes mellitus patients attended at Jugol General Hospital in eastern Ethiopia Methods A retrospective cross-sectional study was conducted among 423 patients with type 2 diabetes mellitus who received follow-up care from 1 June 2017 to 1 June 2022. The study participants were enrolled consecutively using a convenience sampling technique. The data were extracted from patients’ medical records using a data abstraction checklist. The extracted data were entered into EpiData, version 3.1, and exported to Statistical Package for the Social Sciences (SPSS), version 22, for analysis. Associations were considered to be statistically significant at a p-value < 0.05 and presented as adjusted odds ratios and 95% confidence intervals. Result The medical records of 423 patients were reviewed. The review revealed that medical records were complete for 410 of these patients, and these records were included in the analysis. The majority of the study participants were female (72.2%) and between the age of 40 and 65 years (61.2%). All of the study participants were eligible for statin prescription; however, statins were prescribed for only 257 (62.7%) study participants. Of the statins prescribed, moderate-dose-intensity statins were prescribed for 40 (15.6%) participants who were at high risk of cardiovascular disease. Atorvastatin was the most commonly (93.3%) prescribed statin. The presence of hypertension, coronary artery disease, and cerebrovascular events was significantly associated with statin prescribing. Conclusion The magnitude of prescribing statins for patients with type 2 diabetes mellitus was low in comparison with the clinical practice guidelines recommendation. This finding is alarming and is a call for action to improve the execution of clinical practice guidelines for the benefit of this high-risk population.